2015
DOI: 10.11118/actaun201462061279
|View full text |Cite
|
Sign up to set email alerts
|

Do Women Really Face Wage Discrimination on the Labour Market? An Analysis Using Intra-household Specialization

Abstract: This study aims to estimate the gender pay gap, cleansed at least partially of the eff ect of intrahousehold specialization on productivity. The estimate is based on EU-SILC data for 19 member countries of the European Union. We use an estimate of the average treatment eff ect on the treated, supplemented by a matching procedure to estimate the unexplained part of the gender pay gap and use a subsample of employees earning more than their partners, thus minimizing the impact of childand family-care on the gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…To establish the unexplained part of the gender pay gap, we estimate the ATT, as did Jurajda and Paligorova (2009) or Hedija (2014, 2015, for example. ATT reflects the part of the raw gender pay gap which could not be explained by differences in the known observed characteristics of men and women in the sample and which could be the result of wage discrimination against women.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To establish the unexplained part of the gender pay gap, we estimate the ATT, as did Jurajda and Paligorova (2009) or Hedija (2014, 2015, for example. ATT reflects the part of the raw gender pay gap which could not be explained by differences in the known observed characteristics of men and women in the sample and which could be the result of wage discrimination against women.…”
Section: Methodsmentioning
confidence: 99%
“…There are a large amount of studies that are devoted to the identification of the causes of the existing gender wage differences. Despite many differences among the individual studies, they all conclude that a certain part of the wage differences between men and women remains unexplained (for example Oaxaca, 1973;Blinder, 1973;Pena-Boquete et al, 2010;Mysíková, 2012;Hedija, 2014). The existence of the unexplained portion is then attributed to unobservable differences in the characteristics of men and women, household-specific factors or to discrimination against women.…”
Section: Unexplained Wage Differences Between Men and Womenmentioning
confidence: 99%
“…To cleanse the wage differences between men and women at least partially of the effect of intra-household specialization on productivity and work effort, Hedija (2014) estimated the gender pay gap using subsample of employees earning more than their partners assuming that the larger part of care for the household and children is taken up by the partner earning less. Using the European Union Statistics on Income and Living Conditions (EU-SILC) data for 19 member countries of the European Union, she concluded that the unexplained part of gender pay gap amounted approximately 10 percent working to the disadvantage of women.…”
Section: Introductionmentioning
confidence: 99%
“…Statistics show that women in developed countries earn less on average than men do even though the right to non‐discrimination and equal pay for equal work is rooted in the law of these countries. Empirical studies show that approximately half of the gender pay gap may be explained by different characteristics of men and women, although there are significant differences among countries (Christofides, Polycarpou, & Vrachimis, ; Hedija, ; Oaxaca, ). The rest of wage differences is often attributed to differences in unobservable characteristics of individuals and wage discrimination against women (Hedija, ).…”
Section: Introductionmentioning
confidence: 99%